Habilidades de indagación científica y logro de aprendizaje en el área de ciencia y tecnología en niños de la Institución Educativa Inicial N°436 San Antonio, Caballococha 2024 - Sánchez Panduro, Mayoly (2024)
The purpose of the research is to establish the relationship between the level of scientific inquiry skills and learning achievement in the area of science and technology in children of the Institución Educativa Inicial N°436 San Antonio Caballococha 2024. The approach is quantitative and The type of research is relational with a non-experimental design, the population was 128 children between the ages of 3, 4 and 5 years. The technique used was for observation, the observation guide was used, being validated by three experts in the field. The result was obtained if the coefficient of 0.768 indicates a high correlation, the p value of 0.05 is fair. It is concluded by accepting the main hypothesis. There is a significant relationship between scientific inquiry skills and learning achievements in the area of science and technology in children.